Transformasi Digital Sebagai Pilar Penguatan Peran Ma'had Al-Jami'ah IAIN Pontianak dalam Masyarakat 5.0 - Prihantono; Handayani, Rini; Kurniawan, Tio Rizki; Imansyah, Teguh; Arnita, Teti; Nursanti; Selamet (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Digital transformation and the Society 5.0 paradigm require Islamic educational institutions to adapt strategically, not only in terms of technology, but also in values, ethics, and their social role. Ma’had Al-Jami’ah IAIN Pontianak, as an institution for character, spiritual, and intellectual development, holds a strategic position in preparing students to become navigators of digital change. This Community Service with Scientific Orientation (PKM-KI) was carried out in the form of a socialization program entitled “Digital Transformation as a Pillar for Strengthening the Role of Ma’had Al-Jami’ah IAIN Pontianak in Society 5.0”, targeting Ma’had administrators, musyrif/musyrifah, and resident students. The methods used included interactive lectures, presentation of national digital data, group discussions, and participatory approaches in a two-hour session. The results indicate five main outcomes: (1) increased awareness of the urgency of digital adaptation within Ma’had; (2) better understanding of the concept and position of Society 5.0; (3) strengthened digital literacy, ethics, and cyber security awareness, leading to the initiative to formulate a Ma’had Digital Ethics SOP; (4) broader insight into digitalpreneurship opportunities and the use of creative content as a medium for da’wah, education, and the creative economy; and (5) growing awareness of the importance of a collaborative digital ecosystem involving Ma’had, the wider campus, communities, government, and industry. Overall, this PKM-KI program provides an initial foundation for strengthening the role of Ma’had Al-Jami’ah in shaping adaptive, competitive, and solution-oriented students in the era of Society 5.0.